The compliance factors of motor vehicle tax payments in Central Java Province - Sunaningsih, Suci Nasehati; Khotijah, Siti Afidatul; Priyono, Nuwun (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2024)
The number of motorized vehicles is always increasing, which is used by local governments to optimize regional tax revenues through Motor Vehicle Tax. The Covid-19 pandemic has had an impact on the emergence of government programs to ease the burden on society through amnesty of fines, known as tax bleaching. Restrictions on activities due to the pandemic have also encouraged local governments to innovate by creating application-based online tax payment systems. This research aims to analyze the influence of Modernization of the Tax Administration System, Service Quality, and Tax Bleaching on Compliance with Motor Vehicle Tax Payments in Central Java Province. The method used is a quantitative method using primary data through distributing questionnaires. The sampling method used a simple random sampling technique and data obtained from 522 respondents. Data analysis uses multiple linear regression. The results of the analysis show that the variables Modernization of the Tax Administration System, Service Quality, and Tax Bleaching have a positive and significant effect on compliance of Motor Vehicle Tax payments in the Central Java Province region.